SITASI PENELITI UNIVERSITAS AIRLANGGA (BIDANG SOCIAL SCIENCE) TAHUN 2018 DI DATABASE SCOPUS SERTA KORELASINYA DENGAN JURNAL YANG DILANGGAN OLEH PERPUSTAKAAN UNIVERSITAS AIRLANGGA - Prasetyo Adi Nugroho (Perpustakaan Nasional RI, 2020)
For Airlangga University, scientific publications have become the identity of institutions and the main indicators for consideration of the government in improving the quality of education and research in Indonesia.A review of the publication of citations of the scientific work of Airlangga University researchers has been carried out which has been indexed by the Scopus database. The study was conducted in October 2019 using the Scopus database using the keywords Airlangga University. The study aims to find out to find out the research citations (social science field) Airlangga University in 2018 indexed in Scopus is associated with journals that are subscribed to the Airlangga University Library. Available data are separated based on the research subject, type of document, name of publication, faculty and citation. analyzed using descriptive analysis. The results of the study illustrate: 1. Airlangga University research subjects in the field of (social science) in Scopus in 2018 the most in the field of Social Science as many as 39 (35%). 2. Type of publication documents from Airlangga University researchers in the field of social science in Scopus in 2018, the most in the field of 79 documents (94%), the others are proceedings and books. 3. Journal which contains the publication of Airlangga University researchers in the field of social science in Scopus in 2018 at most is the journal Pertanika Journal of Social Sciences and Humanities from Malaysia. 4. The most productive faculty of Airlangga University in the field of social science in Scopus Tahun 2018 is the Faculty of Economics and Business (FEB) which produces 61 documents (43%). 5. Citation of Airlangga University researchers in the field of (social science) in Scopus 2018 associated with journals that are subscribed to by the library is very minimal.